Determination of liquefaction potential for two selected sites in Kerbala city- middle of Iraq - Abdullah, Hamed; Fattah, Mohammed; Abed, Abdulkareem (International Journal of Engineering and Technology, 2017)
Geotechnical characterization of the sites has been investigated with the collection of borehole data from different sources. Using the data, grain size distribution curves have been developed to understand the particle size distribution of the alluvium present. These curves were further used for preliminary assessment of liquefiable areas. From geotechnical characterization, it has been observed that the soil profile in the two sites is dominated by sand and silty sand.Seed and Idriss (1971) approachhas been usedevaluatethe liquefaction potentialbydeterminationof the relation between the maximum ground acceleration (a max/g) valuesdue to an earthquake and the relative density of a sand deposit in the field. The results reveal that the study area will be subjected to occurrence of liquefaction under an earthquake of maximum ground acceleration of 0.1 g when the soil is loose with a relative density between (25-40) % in Kerbala city.Design chartswere obtained for determination of liquefaction potentialin any layer with knowingthe field relative densityand the value of the maximum ground surface acceleration.